WHO Grade Loses Its Prognostic Value in Molecularly Defined Diffuse Lower-Grade Gliomas - Carstam, Louise; Corell, Alba; Smits, Anja; Dénes, Anna; Barchéus, Hanna; Modin, Klara; Sjögren, Helene; Ferreyra Vega, Sandra; Bontell, Thomas Olsson; Carén, Helena; Jakola, Asgeir Store (Frontiers in Oncology, 2022)
Background While molecular insights to diffuse lower grade glioma (dLGG) have improved the basis for prognostication, most established clinical prognostic factors come from the pre-molecular era. For instance, WHO grade as a predictor for survival in dLGG with isocitrate dehydrogenase (IDH)-mutation has recently been questioned. We studied the prognostic role of WHO grade in molecularly defined subgroups and evaluated earlier used prognostic factors in the current molecular setting. Material and methods A total of 253 adults with morphological dLGG, consecutively included between 2007-2018, were assessed. IDH-mutations, codeletion of chromosomal arms 1p/19q and cyclin-dependent kinase inhibitor 2A/B (CDKN2A/B) deletions were analyzed. Results There was no survival benefit for patients with WHO grade 2 over grade 3 IDH-mut dLGG after exclusion of tumors with known CDKN2A/B homozygous deletion (n=157) (log-rank p=0.97). This was true also after adjusting for oncological post-operative treatment and when astrocytomas and oligodendrogliomas were analyzed separately. In IDH-mut astrocytomas, residual tumor volume after surgery was an independent prognostic factor for survival (HR 1.02; 95% CI 1.01-1.03; p=0.003), but not in oligodendrogliomas (HR 1.02; 95% CI 1.00-1.03; p=0.15). Preoperative tumor size was an independent predictor in both astrocytomas (HR 1.03; 95% CI 1.00-1.05; p=0.02) and oligodendrogliomas (HR 1.05; 95% CI 1.01-1.09; p=0.01). Age was not a significant prognostic factor in multivariable analyses (astrocytomas p=0.64, oligodendrogliomas p=0.08). Conclusion Our findings suggest that WHO grade is not a robust prognostic factor in molecularly well-defined dLGG. Preoperative tumor size remained a prognostic factor in both IDH-mut astrocytomas and oligodendrogliomas in our cohort, whereas residual tumor volume predicted prognosis in IDH-mut astrocytomas only. The age cut-offs for determining high-risk in patients with IDH-mut dLGG from the pre-molecular era are not supported by our results.